Performance Evaluation of an Optoelectronic Oscillator Based on a Band-Pass Microwave Photonic Filter Architecture - Gabriela Correa-Mena, Ana; Enrique Zaldivar-Huerta, Ignacio; Lee, Min Won; Garcia-Juarez, Alejandro; Garcia-Delgado, Luis A. (Společnost pro radioelektronické inženýrství, 2017)
The experimental performance evaluation of an optoelectronic oscillator based on a band-pass microwave photonic filter architecture is carried out. The novelty of this proposal resides in the fact that the architecture used allows enhancing the free spectral range of the optoelectronic oscillator. Considering the optical spectral characteristics of the multimode laser diode used as an optical source, the length and the chromatic dispersion parameter of the optical fiber which acts as a feedback loop, it is possible to determine the appearance of a series of spectrally pure microwave signals widely spaced. In particular, the experimental results show a phase noise as low as -92.69 dBc/Hz at 10 kHz offset frequency from the 2.26 GHz carrier for an optical delay line of 25.24 km and a Q factor of 2.04×109.
Keywords: Optoelectronic oscillator; band-pass microwave photonic filter; microwave signals; phase noise.